MEMOTIVASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN COOPERATIVE TIPE SCRIPT PADA MATERI SPLDV DI KELAS VIII SEMESTER I SMP NEGERI 3 KUBU - Cahye, Cahye (Jurnal Pendidikan Matematika dan IPA, 2018)
This research background was by low motivation to learn mathematics in the classroom. This classroom action research is aimed to improve the motivation to learn mathematics of VIII grade SMP Negeri 3 Kubu. Classroom action research done in two cycles with 30 students. Techniques of collecting data is observation by researchers and collaborators. The data was analyzed qualitatively with the data source from the observer. The success of the model Cooperative script in declared successful, less successful or unsuccessful. Motivation indicators defined by the researchers themselves with â‰¥ 60% of students motivated. Indicators of motivation in this research there are four, namely: 1). Responsible, 100% 2). Challenges, 70%, 3). Inovatif, 63%, 4). Competitive, 80%. Thereby motivating student learning using Cooperative learning model type of script can improve mathematics learning in the classroom.Keywords: Student motivation, learning models Cooperative script.